2010
DOI: 10.1309/ajcpbwjp3cg6jzka
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Biopsy of the Distal Extremities

Abstract: We reviewed our cytopathology databases for an 11-year period to identify all fine-needle aspiration biopsy (FNAB) cases of palpable masses of the hand, wrist, ankle, or foot. Cases were included only if there was a subsequent tissue biopsy or a minimum 1-year clinical follow-up. Of 141 aspirates, 41, 23, 34, and 43 were from the hand, wrist, ankle, and foot, respectively. Specific benign or malignant diagnoses were achievable in 71.6% of cases, whereas the remaining cases were given a descriptive diagnosis (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
2
16
0
1
Order By: Relevance
“…Other lesions encountered for FNAC at these sites (but not seen in our study) reported by other studies include viral infections (herpes and molluscum contagiosum), angioma, glomus tumor, and skin carcinomas …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Other lesions encountered for FNAC at these sites (but not seen in our study) reported by other studies include viral infections (herpes and molluscum contagiosum), angioma, glomus tumor, and skin carcinomas …”
Section: Discussionsupporting
confidence: 62%
“…Lesions in the hand and wrist are commonly encountered in clinical practice. Being exposed, these sites are prone to trauma, reactive, reparative and infectious processes which may form mass lesions mimicking neoplasia and prompting immediate work up . Most of these lesions are readily accessible to FNAC, which can be used as a primary diagnostic modality in most of them.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity, that is, the ability to distinguish between benign and malignant lesions, among the authors who expressed these data from their populations, ranged from 65 3 to 100%, 10,11,22 which is close to those of the more invasive methods.…”
Section: Discussionmentioning
confidence: 62%
“…Unfortunately, in that paper, the analysis was limited to soft tissue metastases only, and the presence of lymph node and skeletal involvement outside the standard FOV was not assessed. Other case studies have reported that lymphomatous involvement can occur in popliteal lymph nodes (11, 12) and distal skeletal bones (13–16). Although these case studies only show selective clinical examples, they were also seen in the present, prospective study.…”
Section: Discussionmentioning
confidence: 99%